2019
DOI: 10.32674/jis.v9i4.391
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assessment of Japanese Students’ Intercultural Competence Developed Through Study Abroad Programs

Abstract: This study explores the factors of study abroad programs that contribute to cultivating intercultural competence. Through an empirically based quantitative examination of 303 Japanese study abroad students, it attempts to gain an understanding of the factors that enhance the development of intercultural competence. Considering that many previous studies worked with students in English-speaking countries, this study examines whether an investigation of Japanese students would yield similar results, given the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…SA experiences have also been found to have positive effects on attitudes towards the target culture and target population, which in turn affected socialization and linguistic gains (Paris, Nyaupane, & Teye, 2014;Streitwieser & Light, 2018;Watson & Wolfel, 2015;Zaykovskaya, Rawal, & De Costa, 2017). It has also been noted that the environment, program type, and predeparture orientations played significant roles in the development of intercultural competence (Hanada, 2019;Nowlan, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SA experiences have also been found to have positive effects on attitudes towards the target culture and target population, which in turn affected socialization and linguistic gains (Paris, Nyaupane, & Teye, 2014;Streitwieser & Light, 2018;Watson & Wolfel, 2015;Zaykovskaya, Rawal, & De Costa, 2017). It has also been noted that the environment, program type, and predeparture orientations played significant roles in the development of intercultural competence (Hanada, 2019;Nowlan, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The score grew by −4.17 points. For the interpretation, Hanada (2019) mentioned that there are two growth curves of students’ perceptions of different cultures: linear curve or up-and-down curve through the analysis of Japanese students of intercultural learning. In intercultural immersion, the latter curve is likely to happen as it is mainly related to a student’s psychological changes.…”
Section: Resultsmentioning
confidence: 99%
“…Deardorff (2015b) addressed the need for intercultural intervention to lead students to have profound cultural experiences. Also, Hanada (2019), which focused on the intercultural learning of Japanese study abroad students, indicated that cultural intervention is one of the essential factors to enhance intercultural understanding. However, only 177 of the 303 students from 13 different Japanese universities collected in this study were provided with some form of intercultural intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the broad literature of international programs, previous studies mostly investigated the impact of students' international experiences using large-scale quantitative surveys (e.g. Rust et al, 2013;Scally, 2015;Nguyen, 2017;Hanada, 2019;DeGraaf et al, 2013); explored the experiences of students in North American, European and Australian contexts (e.g. Cushner and Chang, 2015;Bloom and Miranda, 2015;Forsey et al, 2012;Santoro, 2014) or studied the predeparture and preparation experiences of students for studying abroad (e.g.…”
Section: Introductionmentioning
confidence: 99%